The End of Derivatives? What the European Union Model Forebodes, and the Subsequent Stock Market Effect (Global Journal of Management and Business Research, 2016)
In 2011 The European Union Tax Commission proposed the establishment of a Financial Transaction Tax (FTT). The FTT was subsequently implemented in France (8/1/12) and Italy (1/1/13). It is also scheduled to be adopted in 9 other European Union states during 2015. Great Britain has thus far failed to accept such a tax. The purpose of the FTT is twofold; minimize and control derivative trading by taxing it, and raise revenues. Opponents of the FTT have suggested that such a tax would increase volatility (i.e., risk) in the securities market and would also lead to a reduction in security trading and a drop in security prices. These are all reasons why Great Britain has thus far refrained from passing the tax.
Keywords: derivatives; security prices; financial transaction tax